Critical Barriers to Realising Inclusive Digital Education in an Urban-Peripheral Context: The Case of Kupang City, Indonesia - Asadoma, Johanis; Liliweri, Aloysius; Pandie, David B.W.; Neolaka, Melkisedek N.B.C. (Journal Public Policy, 2025)
This study examines barriers to implementing inclusive digital education policy in under-resourced, urban-peripheral contexts, focusing on Kupang City in Eastern Indonesia. Despite its urban status, Kupang faces infrastructural fragility, limited institutional capacity, and socio-economic disparities that complicate the translation of national reforms, particularly Merdeka Belajar and the Platform Merdeka Mengajar (PMM), into practice. Using a qualitative single-embedded case study, data were collected through 25 semi-structured interviews with national, municipal, school, and community actors, supplemented by policy documents and statistical records. Guided by Grindle’s policy content–context model, Lipsky’s street-level bureaucracy theory, and van Dijk’s digital inclusion framework, the analysis highlights three interconnected dimensions that sustain policy–practice gaps: governance misalignment, technological deficits, and constrained actor agency and resource support. These produce five barriers: weak coordination, limited teacher capacity, street-level discretion, and reliance on unstable external resources. Findings reveal that limited outcomes are shaped less by isolated technical failures than systemic misalignments, resulting in partial adoption, symbolic compliance, and selective inclusion. The study contributes by extending empirical evidence to an under-researched eastern Indonesian context. It underscores the need for adaptive governance, targeted capacity building, and stable resources to align national ambitions with local realities.